RESPONSE OF COWPEA (VIGNA UNGUICULATA L.) GENOTYPES TO NATIVE SOIL RHIZOBIA FOR NODULATION, YIELD AND SOIL PROPERTIES - BINJOLA, SONAM; KUMAR, NARENDRA (The Bioscan, 2013)
A field experiment was conducted on sandy loam soil, on comparision of both the check varieties, COCP-702 performed significantly better than RC-101 in most of the characters under study. The highest soil microbial biomass carbon, i.e., 234.70 μg g-1, soil available N, i.e., 256.56 kg ha-1 and K, i.e., 205.00 kg ha-1 was shown by check variety COCP-702. PGCP-4 recorded significantly more number of nodules plant-1, i.e., 74.33, N concentration in grain, i.e., 4.76%. PGCP-6 gave significantly more grain yield, i.e., 1893.75 kg ha-1, plant N, i.e., 2.15 %, plant protein content, i.e., 13.43 %. This variety also recorded highest N uptake by grain, i.e., 81.81 kg ha-1 and total plant uptake, i.e., 97.64 kg ha-1. Response of COCP-702, PGCP-4 and PGCP-6 to native soil rhizobia were found to be significantly more than the other cowpea genotypes.